Theatrical characters when Kassem matrod .. Read in the architecture of the composition - Khazaal Mahmoud, Rabie (Journal of College of Education, 2020)
Qassem Muthad's experience in writing the play is a creative achievement in the experiences of Iraqi theater and new lighting, adding to the light spots that excite those interested and engaged in Arab theater in general and Iraqi in particular. Qassem, who was expelled from the theatrical scripts, was able to carve his name on the front of the Iraqi theatrical writing.Qasim is fired in all his plays, including The three texts at which we stopped were the dominant element in the structure of the text,The depth of its semantic dimension and its tragic reality, where it appeared in part characters living in pain, terror, deprivation and alienation, wishing to exist and exercising its awareness despite the state of internal rift that it is experiencing and the state of separation. Characters in their alienation internally and externally, especially those that looked gray in the homeland in her eye, pale narrow and suffocating, distorted features